Pengembangan panduan konseling kognitif behavioral teknik self management untuk meningkatkan motivasi belajar siswa di sekolah menengah pertama - Putra, Cokorda Oka Wibhawa; Dantes, Nyoman; Arwati, Kadek Ari Dwi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research is a development research (research & development). The product developed is Cognitive Behavioral Counseling Guide to Self Management Techniques to Increase Students' Learning Motivation in Class VII. This handbook is designed to assist counseling teachers in providing counseling services in schools, especially in overcoming the problem of low learning motivation in class VII studeints. Thei deiveilopmeint proceidurei in this study useis thei 4D deiveilopmeint modeil proposeid by Thiagarajan, which consists of stageis